The Efficiency of Waqf Practice in Human Resource Development: Evidence from Different Countries - Sidi, Mohamed Khalifa; Rafiq, Mansha (International Journal of Islamic Economics and Governance, 2023)
Waqf is as an Islamic charity foundation for the realization of goals through property and finance allocated to a legal foundation. In Muslim countries, there are many projects [1]that are operated through waqf benefices and assets. Waqf is often channelled to humanitarian projects, cultural, economic, health, education and training, among other social welfare projects. This paper discusses the efficiency of waqf practice in human resource development, particularly in Algeria, Bangladesh, Sudan, Morocco, Indonesia, Singapore, Kuwait and Malaysia. The significance of this paper manifests in its analysis of the waqf models practiced in the sampled countries from which the paper concludes that waqf is inefficiently managed in Indonesia, Bangladesh, Algeria and Morocco. However, waqf is efficiently practiced in Singapore, Kuwait, Sudan and Malaysia. The study raises awareness of the role of waqf in social development. It attempts to define a new approach which attempts to merge waqf models from successful countries with those in which waqf appears to be inefficient particularly in regards to its application for the development of human resources. Furthermore, the paper claims that waqf is the most suitable mechanism for poverty alleviation.